(untitled) (WAKTU: Jurnal Teknik UNIPA, 2010)
In order to identify the requirement, balance and availability analysis of water balance in the Teritip Dam to fulfill the raw water required at administration region of the river basin of the teritip dam. Data which used in this study is Balikpapan’s hidroclimatology, Then the data analysed, to get 10 daily stream discharge with Model F.J. Mock. After got the result of analysis from the water availibility, then continued with dependable discharge analysis with Basic Moon method that use Logarithm Pearson type III distribution, and also tested with Smirnov kosmogorof test. We get the 99 % dependable discharge from year 1983 up to year of 2007 from this calculation that represent the discharge inflow to the dam that represent the dam water availability. The amount of water required is amount of water required in administration region staying Teritip Dam Basin, that located at east Balikpapan District, for example ; Countryside Manggar, Countryside Manggar Baru, Countryside Lamaru, Countryside Teritip to fulfill domestic, industry and non-domestic water requirement untill year of 2015. The Result of this study indicate that the Terit ip Dam water supply can supply the demand of Domestic, non-domestic, and industrial water requirement with 100% reliability, at 2010. The Teritip Dam water supply can supply the demand of Domestic, nondomestic, and industrial water requirement with 100% reliability, at 2011. The Teritip Dam water supply can supply the demand of Domestic, non-domestic, and industrial water requirement with 100% reliability, at 2012. The Teritip Dam water supply can only supply the demand of Domestic, non-domestic, and industrial water requirement with 83% reliability, at 2013. The Teritip Dam water supply can only supply the demand of Domestic, non-domestic, and industrial water requirement with 69% reliability at 2014 The Teritip Dam water supply can only supply the demand of Domestic, non-domestic, and industrial water requirement with 61% at 2015.